2007
DOI: 10.1111/j.1365-3156.2006.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based study on knowledge, attitude and practice on the mode of transmission, prevention and treatment of the Buruli ulcer in Ga West District, Ghana

Abstract: SummaryBuruli ulcer disease (BUD), a devastating tropical disease caused by Mycobacterium ulcerans, occurs in more than 80% of the administrative districts of Ghana. To elucidate community perceptions and understanding of the aetiology of BUD, attitudes towards Buruli patients and treatment-seeking behaviours, we conducted a survey with 504 heads of households and seven focus group discussions in Ga West District, Ghana. Although 67% of participants regarded BUD as a health problem, 53% did not know its cause.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
85
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 31 publications
12
85
2
6
Order By: Relevance
“…Our study complements findings of earlier sociocultural studies of Buruli ulcer 3,9,16,17 and clarifies help-seeking for preulcers and ulcers of persons affected by Buruli ulcer. This information is critical for health programming in the Ga-West and Ga-South municipalities, where sociocultural research has been lacking.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Our study complements findings of earlier sociocultural studies of Buruli ulcer 3,9,16,17 and clarifies help-seeking for preulcers and ulcers of persons affected by Buruli ulcer. This information is critical for health programming in the Ga-West and Ga-South municipalities, where sociocultural research has been lacking.…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, 72% of respondents said there was no program in place to address Buruli ulcer. 9 Since then, there has been a public health initiative to create awareness about Buruli ulcer and availability of medical care, improve case-management, and access to care. Our study not only supports previous findings of this study 9 about herbal medicine as the first treatment choice, but shows evidence of increasing awareness and use of medical treatment, and clarifies current treatment needs and gaps for Buruli ulcer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most socio-cultural and economic studies on BU reported on local perceptions (beliefs, knowledge and attitudes), and social and economic burdens of the disease to patients and their families (Ahorlu et al, 2013;Stienstra et al, 2002;Adamba & Owusu, 2011;Peeters et al, 2008;Renzaho et al, 2007;Debacker et al, 2004;Aujoulat et al, 2003;Bigelow et al, 2002;Asiedu & Atuaful, 1998). This paper on the other hand focused on identifying social and economic factors that are considered when the affected and infected are making health seeking decisions on where and when to seek for health.…”
Section: Discussionmentioning
confidence: 99%